2005
DOI: 10.1093/nar/gki847
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conservation suggests a regulatory function of AUG triplets in 5'-UTRs of eukaryotic genes

Abstract: By comparing sequences of human, mouse and rat orthologous genes, we show that in 5′-untranslated regions (5′-UTRs) of mammalian cDNAs but not in 3′-UTRs or coding sequences, AUG is conserved to a significantly greater extent than any of the other 63 nt triplets. This effect is likely to reflect, primarily, bona fide evolutionary conservation, rather than cDNA annotation artifacts, because the excess of conserved upstream AUGs (uAUGs) is seen in 5′-UTRs containing stop codons in-frame with the start AUG and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
82
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 67 publications
14
82
1
2
Order By: Relevance
“…We found evidence for strong purifying selection against uAUGs in yeast 59 UTRs, an observation that is consistent with previous studies (Churbanov et al 2005;Iacono et al 2005). In agreement with Churbanov et al, we also found that, for the 20% of genes in yeast that do contain uAUGs in their 59 UTRs, these trinucleotides tend to be conserved, suggesting that while in general uAUGs are deleterious, for a subset of yeast genes, they play an important regulatory role that confers a selective advantage to the organism.…”
Section: Discussionsupporting
confidence: 93%
“…We found evidence for strong purifying selection against uAUGs in yeast 59 UTRs, an observation that is consistent with previous studies (Churbanov et al 2005;Iacono et al 2005). In agreement with Churbanov et al, we also found that, for the 20% of genes in yeast that do contain uAUGs in their 59 UTRs, these trinucleotides tend to be conserved, suggesting that while in general uAUGs are deleterious, for a subset of yeast genes, they play an important regulatory role that confers a selective advantage to the organism.…”
Section: Discussionsupporting
confidence: 93%
“…Previous work reported that AUG triplets are depleted from mammalian transcript leaders, yet they are also highly conserved (Churbanov et al 2005). Although similar results were reported in yeast, only about 250 genes had annotated transcript leaders at the time.…”
Section: Evolutionary Comparisons Of Yeast Transcript Leaderssupporting
confidence: 74%
“…(41,(67)(68)(69) Functional roles of many uORFs and uORFencoded peptides were predicted with the aid of various computational approaches. (78)(79)(80)(81)(82) It was found that some orthologous eukaryotic genes are characterized by conservative uAUG triplets, which suggests their importance in expression control. (78) Similarly, ca.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
“…(78)(79)(80)(81)(82) It was found that some orthologous eukaryotic genes are characterized by conservative uAUG triplets, which suggests their importance in expression control. (78) Similarly, ca. 200 uORF-encoded peptides were characterized by a high level of evolutionary conservation between human and mouse genes, which allows the assumption of their functional significance.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%